2006
DOI: 10.1159/000089934
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the GABAergic System on Memory Formation and State-Dependent Learning Induced by Morphine in Rats

Abstract: In the present study, the effects of intraperitoneal injections of GABAA receptor agonist and antagonist on memory formation and morphine state-dependent learning were investigated in rats. Pre-training administration of morphine (1–15 mg/kg) in a step-down passive avoidance task induced state-dependent learning with impaired memory retrieval on the test day. The impairment of memory was restored after the pre-test administration of the same dose of morphine. The pre-test administration of the GABA<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 102 publications
1
16
0
Order By: Relevance
“…This may be in agreement with our previous report that systemic administration of muscimol inhibited the similar morphine response (Zarrindast et al 2006b). GABA and opioid receptors exert interactions in different ways.…”
Section: Discussionsupporting
confidence: 94%
“…This may be in agreement with our previous report that systemic administration of muscimol inhibited the similar morphine response (Zarrindast et al 2006b). GABA and opioid receptors exert interactions in different ways.…”
Section: Discussionsupporting
confidence: 94%
“…4A). State-dependent learning denotes the fact that information that has been learned while an animal is under the influence of a certain drug (state) can only be recalled when the animal is in the same state in which the information was learned, not in a different (i.e., undrugged) state (Zarrindast et al, 2006). The mice infused with 10 nmol of KN93 before both the training and test trials showed a significantly prolonged finding latency in the test trial compared with the mice treated with vehicle (data not shown).…”
Section: Pcp Impairs Latent Learning and Dopamine-nmda Signaling 1601mentioning
confidence: 99%
“…Moreover, various GABA analogs and agents affecting transmitter metabolism to enhance GABAergic tone have been reported to exert anxiolytic effects [98, 102107]. The role of GABA in learning and memory has also been widely recognized [2830, 90, 100, 108112]. Three comprehensive reviews particularly [12, 17, 113] emphasize the role of central GABA in memory-anxiety interplay, noting amnestic/anxiolytic effects of positive, and opposite profiles of negative, GABA modulators (also see [2730, 111, 114, 115] for details).…”
Section: Neurochemistry and Neurogenetics Of Memory And Anxietymentioning
confidence: 99%